Determinants of Stock Returns: A Comparison of Microeconomic and Macroeconomic Factors - Annisa, Mutia Rakhmi; Arifin, Zaenal (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to examine the effect of microeconomic and macroeconomic factors on stock returns and determine which factors are more dominant. This topic is important because identifying the determinants of stock returns can support investors in making informed investment decisions and enrich empirical evidence from emerging capital markets. The microeconomic variables analyzed include profitability, trading volume, and dividend policy, while the macroeconomic variables consist of inflation, interest rates, and exchange rates. The study uses secondary data obtained from company financial reports of firms listed in the LQ45 Index on the Indonesia Stock Exchange. The data are analyzed using panel data regression with the Random Effect Model (REM) approach. The results show that profitability, trading volume, and dividend policy have a positive and significant effect on stock returns. Inflation and interest rates do not have a significant effect on stock returns. In contrast, the exchange rate has a negative and significant effect on stock returns. Overall, microeconomic factors are more dominant than macroeconomic factors in explaining stock returns.